New development: Responding to complexity in public services—the human learning systems approach. Issue 7 (3rd October 2021) - Lowe, Toby; French, Max; Hawkins, Melissa; Hesselgreaves, Hannah; Wilson, Rob
Abstract : IMPACT: Current approaches to public management based on principles of marketization, management and measurement are increasingly being seen to fail when faced with the complex world of public services. The Human Learning Systems (HLS) concept represents an alternative approach which embraces the complexity of the real world of organizations working to deliver services. Produced in collaboration with an emerging community of funders, managers and commissioners of services, HLS offers a framework which bridges academic complexity theory and the diverse contexts of practice. This article introduces HLS as a means to enable organizations, practitioners and service users to work together more effectively. ABSTRACT: The challenges facing public services and non-profit organizations are complex and multi-faceted, confounding the orthodoxies of bureaucratic public administration and New Public Management approaches. This article discusses the merits and potential of the emerging 'Human Learning Systems' (HLS) approach to the funding, commissioning and management of public services as an alternative management logic. Building on prior introductory work, the authors analyse the current state of development, content and operation of HLS and its collaborative process, involving more than 300 organizations. Drawing on the experience of public and non-profit service professionals in adopting and experimenting with this approach, the authors found that HLS can provide a helpful and innovative conceptual frame to promote constructive engagement with complexity in public management theory and practice.